Host genetics and diet composition interact to modulate gut microbiota and predisposition to metabolic syndrome in spontaneously hypertensive stroke‐prone rats. Issue 6 (1st March 2019) - Singh, Arashdeep; Zapata, Rizaldy C.; Pezeshki, Adel; Workentine, Matthew L.; Chelikani, Prasanth K.
ABSTRACT: Metabolic syndrome encompasses obesity, glucose intolerance, hypertension, and dyslipidemia; however, the interactions between diet and host physiology that predispose to metabolic syndrome are incompletely understood. Here, we explored the effects of a high‐fat diet (HFD) on energy balance, gut microbiota, and risk factors of metabolic syndrome in spontaneously hypertensive stroke‐prone (SHRSP) and Wistar‐Kyoto (WKY) rats. We found that the SHRSP rats were hypertensive, hyperphagic, less sensitive to hypophagic effects of exendin‐4, and expended more energy with diminished sensitivity to sympathetic blockade compared to WKY rats. Notably, key thermogenic markers in brown and retroperitoneal adipose tissues and skeletal muscle were up‐regulated in SHRSP than WKY rats. Although HFD promoted weight gain, adiposity, glucose intolerance, hypertriglyceridemia, hepatic lipidosis, and hyperleptinemia in both SHRSP and WKY rats, the SHRSP rats weighed less but had comparable percent adiposity to WKY rats, which supports the use of HFD‐fed SHRSP rats as a unique model for studying the metabolically obese normal weight (MONW) phenotype in humans. Despite distinct strain differences in gut microbiota composition, diet had a preponderant impact on gut flora with some of the taxa being strongly associated with key metabolic parameters. Together, we provide evidence that interactions between host genetics and diet modulate gut microbiota and predispose SHRSP rats to develop metabolic syndrome.—Singh, A., Zapata, R. C., Pezeshki, A., Workentine, M. L., Chelikani, P. K. Host genetics and diet composition interact to modulate gut microbiota and predisposition to metabolic syndrome in spontaneously hypertensive stroke‐prone rats. FASEB J. 33, 6748–6766 (2019). www.fasebj.org